Do discurso publicitário de origem popular: O anúncio de videntes (Revista de Estudos da Linguagem, 1995)
lnthis paper, I examine the question ofsubjectivity in advertisements for clairvoyants, according to Discourse Analysis Theory (French version) and some elements of Enunciation Theory. These advertisements result from the interrelation between two kinds of discourse, the advertising andthe spiritualistic, as manifested inlower class publications. I show that, in spite ofits popular origin, this kind ofpropaganda in fact repeats the patternofthe elite class - with its ideology orpower, domination and alienation, both in linguistic and discourse terms.